A confessional account of community entry: doing critically reflexive ICT4D work in a deep rural community in South Africa*. Issue 3 (3rd July 2018) - Krauss, Kirstin E. M.
ABSTRACT: In this paper I reflect on the community entry phases of doing a critical ethnography in a traditional Zulu community in a deep rural part of South Africa. I present my reflections in the form of confessional narratives on community entry and on how an Information Communication Technology for Development (ICT4D) project was introduced in the community. Drawing on a basic principle of doing social science research, I ask: In what ways should I achieve self-emancipation, in order to ensure the on-going emancipation and empowerment of the people I engage with? I also ask: How should one do critically reflexive community entry and ICT4D project introduction in communities that embrace a people-orientated worldview? The paper is practice-orientated in that it demonstrates critical self-reflexive community entry in a particular ICT4D project situation, how community entry encounters informed follow-up work, and how cultural interpreters empowered me to do community entry successfully. Methodologically, the paper contributes by demonstrating the value of using narrative examples to represent virtuoso expertise of how I developed knowledge of self-reflexivity while excavating hidden social meanings from an ICT4D project situation.